Surveying managers to inform a regionally relevant invasive Phragmites australis control research program. (15th January 2018) - Rohal, C.B.; Kettenring, K.M.; Sims, K.; Hazelton, E.L.G.; Ma, Z.
Abstract: Managers of invasive species consider the peer-reviewed literature only moderately helpful for guiding their management programs. Though this "knowing-doing gap" has been well-described, there have been few efforts to guide scientists in how to develop useful and usable science. Here we demonstrate how a comprehensive survey of managers (representing 42 wetland management units across the Great Salt Lake watershed) can highlight management practices and challenges (here for the widespread invasive plant, Phragmites australis, a recent and aggressive invader in this region) to ultimately inform a research program. The diversity of surveyed organizations had wide-ranging amounts of Phragmites which led to different goals and approaches including more aggressive control targets and a wider array of control tools for smaller, private organizations compared to larger government-run properties. We found that nearly all managers (97%) used herbicide as their primary Phragmites control tool, while burning (65%), livestock grazing (49%), and mowing (43%) were also frequently used. Managers expressed uncertainties regarding the timing of herbicide application and type of herbicide for effective control. Trade-offs between different Phragmites treatments were driven by budgetary concerns, as well as environmental conditions like water levels and social constraints like permitting issues. Managers had specific ideas about the plant communities they desired following Phragmites control, yet revegetation of native species was rarely attempted. The results of this survey informed the development of large-scale, multi-year Phragmites control and native plant revegetation experiments to address management uncertainties regarding herbicide type and timing. The survey also facilitated initial scientist-manager communication, which led to collaborations and knowledge co-production between managers and researchers. An important outcome of the survey was that experimental results were more pertinent to manager needs and trusted by managers. Such an approach that integrates manager surveys to inform management experiments could be adapted to any developing research program seeking to be relevant to management audiences. Highlights: We present a survey approach for integrating land manager input into scientific research design. Managers reported uncertainties about invasive Phragmites control outcomes and trade-offs. Researchers incorporated manager uncertainties and constraints in Phragmites control research. Managers also assisted with research implementation, thereby co-producing knowledge. Manager involvement increased research relevance and its immediate application through improved management.